Knowledge, Attitudes, and Practices Regarding “New Normal” Guidelines and Quality of Life Among Thai People During the COVID-19 Outbreak: An Online Cross-Sectional Survey - Waewwab, Pathavee; Pan-ngum, Wirichada; Siri, Sukhontha; Bhopdhornangkul, Bhophkrit; Mahikul, Wiriya (Frontiers in Public Health, 2022)
In Thailand, strict prevention and control strategies have been implemented to mitigate the rapid spread of coronavirus disease 2019 (COVID-19). “New normal” guidelines and a series of mobile health applications have been introduced by the healthcare sector and implemented to aid the disease control monitoring and prevention of widespread outbreaks. This study aimed to assess the knowledge, attitudes, and practices (KAP) regarding “new normal” guidelines and quality of life (QOL) among Thai people during the COVID-19 outbreak, and to determine the association between KA, QOL, and practices. An online cross-sectional survey was conducted from 7 June to 12 September 2021 among Thai people in Public Health Region 6 aged ≥ 18 years old. Of the 506 survey participants, 80.3% were female, and 65.0% were 25–59 years old. The survey revealed that 52.2% of participants were classified as having more accurate knowledge, 58.9% were classified as having more positive attitudes, and 80.8% were classified as having more frequent practices regarding “new normal” guidelines, and 54.7% had high QOL. Of the participants, 93.7% agreed that “people who have been fully vaccinated should wear a mask while outside,” and 95.5% wore a face mask outdoors in crowded places. However, 60.9% of participants misunderstood some details regarding online applications for contact tracing and vaccination services, 44.2% felt that these applications were difficult to use, and 33.4% rarely or never downloaded or used these applications. In logistic regression analyses, accurate knowledge of COVID-19 was associated with higher education, being a government employee, monthly family income > 30,000 Thai Baht, and regular use of social media. More positive attitudes regarding “new normal” guidelines and high QOL were associated with positive practices. High QOL was associated with older age, and higher education. Enhancement of attitudes and QOL is also important for improving practices in the general population during the COVID-19 pandemic. Significant factors identified in KAP will be crucial for developing effective prevention and control programs to mitigate the spread of COVID-19. To implement mobile health applications effectively, more work is required to improve the ease of use and promotion strategies.